Electrochemical behavior of some ethylenedioxycoumarins: Cathodic dimerization - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
Electrochemical behavior of recently synthesized 7,8-ethylenedioxy-4-methyl-2(H)-1-benzopyran-2-one, (1), 7,8-ethylenedioxy-2(H)-1-benzopyran-2-one, (2), and 6,7-ethylenedioxy-4-methy1-2(H)-1-benzopyran-2-one, (3) was studied using cyclic voltammetry at a hanging mercury drop electrode and controlled-potential coulometric techniques. The results indicated that an irreversible one-electron cathodic peak was observed for each compound in the potential range from 0.0 to -2.0 V. The coulometric experiments were performed in a low yield and the products were identified by FT-IR spectrometry, H-1 NMR and mass spectrometry. The coulometric results indicated a dimeric product for each compound. A mechanism for the electrodimerization pathway was proposed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ethylenedioxycoumarins; Flavonoids; Cyclic voltammetry; Cathodic dimerization; REDUCTION; MECHANISM; MERCURY; ASSAY; BOND